ONLINE SEXUAL EXPLOITATION OF CHILDREN, IN PARTICULAR THE CRIME OF CHILD PORNOGRAPHY - Katalin Csepregi; István Kovács (Revija za kriminologiju i krivično pravo)
The real challenge is to keep pace with today’s rapidly changing world. However, the development of infocommunication tools and technologies not only brings benefits, it also offers plenty of opportunities for offenders. It is inevitable to use the internet these days, so it is extremely important to lay down the right rules and conditions for children. The most important step we can take against it is prevention and awareness raising. In the study, the authors sought to clarify basic concepts, describe the international environment, and analyze data from Hungary, which manifests itself in the analysis and evaluation of BSR and anonymous judgments.